Prophylactic ligation of uterine arteries at its origin in laparoscopic surgical staging for endometrial cancer. Issue 12 (27th September 2021) - Yavuzcan, Ali; Bakay, Kadir
Abstract: Aim: The aim of this study was to compare the surgical outcomes between patients who were staged laparoscopically for early‐stage endometrioid‐type endometrial cancer (EC) between those who underwent prophylactic ligation of uterine arteries (UAs) prior to pelvic lymphadenectomy and the patients who were operated with standard procedure. Methods: This retrospective study was conducted in women diagnosed with early‐stage and low/intermediate‐risk endometrioid‐type EC. The control group included patients who underwent standard laparoscopic pelvic lymphadenectomy and the study group concerned patients who underwent prophylactic ligation of UA prior to pelvic lymphadenectomy. The prophylactic ligation of UA procedure was performed at a point just proximal to its origin. Results: The mean lymph node count dissected in the study group was higher in terms of statistical significance (17.5 ± 2.2 vs. 19.8 ± 3.6, p = 0.003 and p ˂ 0.05). The rate of the patients who had a positive pelvic lymph node detected did not differ between groups (7.4% vs. 16.7%, p = 0.258 and p ˂ 0.05). The operation time (OT) of the patients in the study group did not differ between groups ( p = 0.546 and p ˂ 0.05). Hemoglobin drop (−0.5 ± 0.7) and hematocrite drop (−0.8 ± 0.9) values in the study group were found to be lower in the study group ( p = 0.000, p = 0.000, and p ˂ 0.05). Conclusions: Performing prophylactic ligation of UA at its origin prevents unwanted bleeding and facilitates the laparoscopic pelvic lymphadenectomy procedure.